USER INTERFACE DESIGN APPLICATION FOR CERAMIC PRODUCT INTRODUCTION AT STUDIO DE'MOZI ART DESIGN - Astuti, Marisa; Anggakarti, Deden Maulana (CENTRAL ASIA AND THE CAUCASUS, 2022)
Ornamental Ceramic is a term for a type of tile made from processed cement and has a visual element on its surface. On the surface there are ornament images, namely decorative images that form decorations with plant patterns such as flowers, leaves and geometric fields, such as triangles, squares and circles. Decorative Ceramics has been around for a long time, found in several areas that have local value as an area that is quite calculated for the existence of the community or an area that has historical value. Decorative ceramics are installed on the wall or floor as a support for decorative elements to create a more memorable space atmosphere.Decorative ceramic crafts in the Cimahi area are very advanced, but this ceramic craft is still a home industry so one of the obstacles is the lack of integration of product sales information to consumers which results in slow orders and buying and selling transactions that have occurred so far. Along with the development of information technology, the craft of decorated ceramics owned by Usaha Micro, Kecil dan Menengah (UMKM) Studio De'Mozi Art Design in Cimahi district wants to try to increase sales of decorated ceramic products by providing the best service through application mediaThis community service activity is carried out on the basis of the need for information on products sold and orders that can be made online. Therefore, a user interface was designed to overcome this problem. The data needed in designing this user interface is the type of product, stock of goods, the production process of goods, prices of goods, production time and how to order With the design of the media user interface for the introduction of decorated ceramic products, it is hoped that it can help UMKM Studio De'Mozi Art Design in introducing Cimahi decorated ceramic products and expanding the marketing area.